Two Cases of Successful Treatment With Hachimijiogan for Irregular Menstruation - Hirabayashi, Tatsuji (Frontiers in Nutrition, 2020)
Hachimijiogan (HJG), a Kampo prescription medication composed of eight crude drugs, has been used for treatment of climacteric disturbance and irregular menstruation. In the Japanese pharmaceutical market, HJG pills consisting of a powdered mixture of these crude drugs are available, as well as a water extract preparation. In this study, two cases of successful treatment with HJG pills are reported. Case 1 was a 37-years-old woman who had irregular menstruation that had previously been treated with HJG extract granules for 3 months; however, her symptoms were not improved. Subsequent treatment with HJG pills at a dose of 40 pills/day for 10 months led to slight improvement of her menstrual cycle, and at a dose of 60 pills/day, her menstrual cycle was normalized. Case 2 was a 29-years-old woman who had irregular menstruation for more than 5 years and was previously treated with HJG extract granules, which led to slight improvement of her symptoms. Her menstrual cycle improved slightly after 9-months treatment with HJG pills at a dose of 40 pills/day and was normalized at a dose of 60 pills/day. This study suggests that the HJG crude drug preparation is more effective than the HJG extract preparation in some cases.